Model documentation of assessment and nursing diagnosis in the practice of nursing care management for nursing students - Hidayat, A. Aziz Alimul; Kes, M. (International Journal of Advanced Nursing Studies, 2015)
Model documentation of assessment and nursing diagnosis in the practice of nursing care management is an integration model in nursing care records, especially records nursing assessment and diagnosis in one format. This model can reduce the duration of the recording in nursing care, and make it easier for students to understand the nursing diagnosis, so that nursing interventions more effective. The purpose of this paper was to describes the form integration documentation of nursing assessment and diagnosis of nursing in nursing care management for nursing students. This literature review was done by searching the following search engine: Pubmed, Midline, EBSCO, and Google Scholar. Data in the synthesis from nursing diagnoses of NANDA-I were incorporated into the of nursing assessment form using Gordon’s functional health pattern. Types of articles included: original research, and literature review. This review of article includes 1) introduction 2) form of nursing assessment documentation 3) implementation of nursing diagnosis documentation 4) the implementation strategy documentation of assessment and nursing diagnosis 5) recommendation for nursing education 6) conclusion.